Pengaruh Ekstrak Buah Lerak (Sapindus rarak) dan Beberapa Adjuvan terhadap Perkecambahan Gulma Fimbristylis miliacea - Pujisiswanto, Hidayat; Nurmiaty, Yayuk; Sriyani, Nanik; Efrima, Annisa (Universitas Lampung, 2021)
Adjuvant is an ingredient added in a formulation to increase the effectiveness of lerak fruit in inhibiting weeds. This study aims to determine the type of adjuvant in lerak fruit extract that can increase the inhibition of germination of Fimbristylis miliacea and to determine the type of adjuvant in lerak fruit extract that is most effective in inhibiting the germination of F. miliacea. The research was conducted from December 2019 to March 2020 in the Weed Laboratory, Faculty of Agriculture, University of Lampung. This study used a Completely Randomized Design (CRD) to determine the type of adjuvant given to lerak fruit extract on F. miliacea germination with 4 replications. The treatments consisted of lerak fruit extract, lerak fruit extract + VCO adjuvant, lerak fruit extract + KAO adjuvant, lerak fruit extract + Polysorbate 80 adjuvant, and control. The Bartlett test was used to test the homogeneity of variance, if the assumptions of the analysis of variance were met, then the mean value of the treatment was continued with the Least Significant Difference (LSD) test at the 5% level. The results showed that adjuvants and without adjuvants added to lerak fruit extract at a concentration of 50% (500 g/l) were able to suppress the percentage of germination and the speed of germination of Fimbristylis miliace seeds.Keywords: adjuvants, lerak fruit extract, Fimbristylis miliacea, weed